Private Investment, Local Government Investment, Village Budget and Economic Growth - Eliza Fazliyaton Alias (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2022)
This study's objective is to determine whether government investment, private investment, and village fund budgets have an impact on economic growth in the West Kalimantan district. The target population in this study were 12 districts in West Kalimantan, namely Bengkayang, Sambas, Landak, Mempawah, Kubu Raya, Sanggau, Sekadau, Sintang, Ketapang, North Kayong, Melawi and Kapuas Hulu districts. The data used in this study are GRDP from BPS, government investment in the form of regional capital expenditures, village funds from the Ministry of Finance of the Republic of Indonesia, and private investment in the form of domestic private investment in each district from the Investment Coordinating Board. This study investigates the topic using quantitative approaches with panel data and verifying the research model with multiple linear regression analysis. The results of the hypothesis test reveal that district government investment in the province of West Kalimantan has no effect on economic growth, and neither does private investment. The relationship between government investment and village funds has no effect (moderation predictor) on economic growth, and neither does the connection between private investment and village funds (moderation predictor). So that economic planning can be accurate, it is planned those future studies will include all parts of Indonesia.